Educational testing and measurement: Classroom application and practice - Kubiszyn, Tom; Borich, Gary (New Jersey, 2007)
Our primary goals for this revision are to (a) provide you with relevant information about the testing and assessment-related aspects of NCLB, (b) help you see how the educational measurement concepts and practices we present in the text apply to NCLB and other accountability requirements, and (c) seamlessly integrate this information throughout the text to help reduce confusion about this complex, far-reaching federal law. to ensure integrated treatment of the measurement implications of NCLB and state high-stakes testing requirements throughout the text, we revised several of the chapters. We also completed a number of updates and additions, which are not specific to NCLB, that were suggested by users of the text.
Keywords: Examination- Measurement; Test Evaluation